Tratamento da dioctofimose em quatis (Nasua nasua) com Ivermectina - Cruz, Aparecida de Cássia dos Santos da [UNIFESP] (2010)
Objectives: To describe Dioctophyma renale sonographic image prior to and during Ivermectin treatment, kidney and liver parenchyma and abdominal cavity sonographic image during the study’s development, to study the red blood cell count, the kidney function by means of creatinine and urea dosing, the liver function by means of ALT (alanine aminotransferase) and alkaline phosphatase dosing, to verify the presence or absence of eggs in the urine parasitology test. Methods: 68 coatis of the Nasua nasua species, adult males and females, raised in the Parque Ecológico do Tietê semi-captivity system were assessed. All animals were weighed, anaesthetized, had a microchip inserted and underwent the following procedures: abdominal ultrasound, urine collection by cystocentesis for the parasitology test and external jugular venipuncture for biochemical analyses (creatinine, urea, ALT and alkaline phosphatase) and red blood cell count. Following ultrasound and urine parasitology test results, the animals were distributed into three groups. Non-parasitized animals were assigned to the SHAM group (n=20) and those parasitized were randomized between PLACEBO (n=24) and IVERMECTIN (n=24) groups. The three groups were randomized for the study time points (7, 14, 21 and 28 days). PLACEBO group animals were treated with 0.9% saline and those of the IVERMECTIN group were treated with Ivermectin. The treatment was performed at zero time point, with repetition on day fourteen. At the end of each period, anaesthetized animals underwent exploratory laparotomy for assessing the abdominal cavity, evidencing the presence or absence of parasites, viability thereof and possible injuries to other organs. Results: 70.6% of the animals were found parasitized. The SHAM group showed normal kidneys and abdominal cavity, as well as laboratory tests, except for slight anemia and eosinophilia. The PLACEBO group showed no difference in the parasite’s sonographic images, confirming vitality thereof by laparotomy. Left kidney hypertrophy and changes in the abdominal cavity were noticed. Laboratory tests showed eosinophilia and hemoglobin and ALT values slightly below the normal limits. On days 14, 21 and 28, the IVERMECTIN group showed differences in sonographic images of parasites located in the right kidney suggesting parasite death, confirmed by laparotomy. Changes in the abdominal cavity and left kidney hypertrophy were noticed. Laboratory tests showed lymphocytosis and hemoglobin, creatinine and ALT values slightly below the normal limits. Conclusions: Differences in sonographic images of parasites were noticed prior to and during Ivermectin treatment. Kidney and liver parenchyma and abdominal cavity ultrasounds evidenced changes in both groups of parasitized animals. Ivermectin-treated animals’ red blood cell count revealed satisfactory results with regard to eosinophilia and lymphocytosis. A slight change in creatinine values of Ivermectin-treated animals was noticed. The urine parasitology test suggested that the positivity may be related to the parasitized location and to the presence of female parasites. PLACEBO and IVERMECTIN groups showed slight changes in the liver function. Ivermectin-treated animals showed satisfactory responses with regard to alkaline phosphatase. Death of parasites located in the kidneys of Ivermectin-treated animals was noticed